Healthy Eating Index-2015 and Dietary Total Antioxidant Capacity as Predictors of Prediabetes: A Case-Control Study - Jamal Rahmani; Karim Parastouei; Maryam Taghdir; Heitor O. Santos; Farinaz Hosseini Balam; Mohsen Saberi Isfeedvajani (International Journal of Endocrinology)
Background. The overall dietary quality, as well as the dietary total antioxidant capacity (DTAC), deserves central attention in the management of borderline high glucose levels since nonpharmacological strategies are imperative in this regard. Thus, we aimed to investigate the association between prediabetes with dietary quality and DTAC. Methods. A case-control study was conducted on 49 patients with prediabetes and 98 controls. Demographics, anthropometric measures, and fasting blood glucose levels of all participants were obtained. Participants completed a validated 80-item food frequency questionnaire (FFQ). DTAC scores were generated using FFQ data, and Healthy Eating Index-2015 (HEI-2015) was used as a diet quality index. The lowest tertile of HEI-2015 and DTAC was considered as the reference category, and logistic regression was used to estimate the relationship between prediabetes with HEI-215 and DTAC. Results. Mean age and body mass index of participants were 47.42 ± 15.98 years and 27.90 ± 4.96 kg/m2. Patients with prediabetes had lower DTAC scores when compared to controls (11.86 ± 5.77 and 17.81 ± 12.08, P = 0.01). There was a significant inverse association between the highest tertile of the DTAC score when compared with the lowest tertile in crude (OR = 0.11; 95% CI: 0.03–0.43), age-adjusted (OR = 0.13; 95% CI: 0.03–0.48), and fully adjusted (OR = 0.09; 95% CI: 0.02–0.53) models. In contrast, there was no difference between HEI-2015 in patients with prediabetes when compared to controls (74.41 ± 8.91 and 74.41 ± 9.35, respectively; P = 0.85). Correspondingly, no difference was observed between the highest tertile of the HEI-2015 score when compared with the lowest tertile in crude (OR = 1.23; 95% CI: 0.53–2.86), age-adjusted (OR = 1.17; 95% CI: 0.48–2.82), and fully adjusted (OR = 1.53; 95% CI: 0.56–4.16) models. Conclusion. This study demonstrates a clear association between prediabetes with less DTAC, but not with HEI-2015.